Motivation Of Fraud: Internal Control System, Organizational Justice, Compensation, And Information Asymmetry - Agoestina Mappadang (Universitas Muhammadiyah Malang, 2022)
The purpose of this research is to analyze the elements that cause an employee or a leader to be motivated so that fraud occurs. The elements in question are compensation, information asymmetry, internal control, and organizational justice. The data for the research was obtained from the collection of questionnaires from a number of 102 resource persons who were employees of BPR Primaesa Sejahtera located in North Sulawesi. For the hypothesis that is tested with multiple regression model (multiple regression model) through SPSS software. The results obtained from the research is that compensation adjustment does not have an effect on the encouragement of fraud asymmetry has a significant positive effect on encouraging organizational control and internal control has a negative effect on the occurrence of incentives. To prevent someone from being compelled to commit fraud within the organization, organizational leaders are required to apply the principles of fairness and effective continuous evaluation in internal control and monitoring of information systems by providing correct information directions in line with organizational needs.